Knowledge, Science and Scientific Knowledge - Ahmad Daud; Maspuroh; Endang Nur Fitriani; Neng Zulfa Alawiyah; Rakha Firjatullah (Bibliotheca: Journal of Philosophy, 2025)
Knowledge is a fundamental aspect of human life that encompasses various forms of information and skills acquired through experience, education, or perception. In this paper, knowledge is categorized into three main types: general knowledge, scientific knowledge, and scientific understanding. Scientific knowledge refers to knowledge obtained through scientific methods, involving systematic testing and observation, while scientific understanding pertains to the results of research processes based on empirical evidence that can be tested and verified. This paper discusses the differences between these three forms of knowledge and highlights the importance of scientific understanding in technological development and modern life. In conclusion, scientific knowledge plays a crucial role in driving innovation and social progress, providing a reliable framework for understanding natural phenomena and improving human quality of life.